A multi-level developmental approach to exploring individual differences in Down syndrome: genes, brain, behaviour, and environment. (September 2020) - Thomas, Michael S.C.; Ojinaga Alfageme, Olatz; D'Souza, Hana; Patkee, Prachi A.; Rutherford, Mary A.; Mok, Kin Y.; Hardy, John; Karmiloff-Smith, Annette; ,
Highlights: A consideration of the causes of individual differences in Down syndrome, at the level of genes, epigenetics, brain, and behaviour, linking potential differences in early development with elevated risk for Alzheimer's disease. Evaluation of environmental (socioeconomic status) and genetic (chromosome 19 apolipoprotein APOE genotype, modulating risk for AD in adulthood) predictors of individual differences in early vocabulary development in a sample of 84 infants and young children with DS. Neither predictor accounted for significant amounts of variance, leaving the wide variability unexplained and likely arising from complex individual effects of the DS genotype. There was weak evidence that early development was faster for the APOE genotype conferring greater AD risk (ε4 carriers) consistent with recent observations in infant attention (D'Souza, Mason et al., 2020 ) Proof of principle that prenatal and neonatal magnetic resonance imaging methods may be used to test the predictive power of measures of early brain structure for variation in DS infant cognitive development. Early brain development represents the concerted effect of the DS genotype. The article argues for the importance of a multi-level, lifespan developmental approach to explore the origins of individual differences in DS cognition. It hypothesises that in this framework, dementia itself may be considered as a developmental disorder (Karmiloff-Smith et al., 2016 ). Abstract: In this article, we focus on the causes of individual differences in Down syndrome (DS), exemplifying the multi-level, multi-method, lifespan developmental approach advocated by Karmiloff-Smith (1998, 2009, 2012, 2016). We evaluate the possibility of linking variations in infant and child development with variations in the (elevated) risk for Alzheimer's disease (AD) in adults with DS. We review the theoretical basis for this argument, considering genetics, epigenetics, brain, behaviour and environment. In studies 1 and 2, we focus on variation in language development. We utilise data from the MacArthur-Bates Communicative Development Inventories (CDI; Fenson et al., 2007 ), and Mullen Scales of Early Learning (MSEL) receptive and productive language subscales (Mullen, 1995 ) from 84 infants and children with DS (mean age 2;3, range 0;7 to 5;3). As expected, there was developmental delay in both receptive and expressive vocabulary and wide individual differences. Study 1 examined the influence of an environmental measure (socio-economic status as measured by parental occupation) on the observed variability. SES did not predict a reliable amount of the variation. Study 2 examined the predictive power of a specific genetic measure (apolipoprotein APOE genotype) which modulates risk for AD in adulthood. There was no reliable effect of APOE genotype, though weak evidence that development was faster for the genotype conferring greater AD risk (ε4 carriers), consistent with recent observations in infant attention (D'Souza, Mason et al., 2020 ). Study 3 considered the concerted effect of the DS genotype on early brain development. We describe new magnetic resonance imaging methods for measuring prenatal and neonatal brain structure in DS (e.g., volumes of supratentorial brain, cortex, cerebellar volume; Patkee et al., 2019 ). We establish the methodological viability of linking differences in early brain structure to measures of infant cognitive development, measured by the MSEL, as a potential early marker of clinical relevance. Five case studies are presented as proof of concept, but these are as yet too few to discern a pattern.